Rapid Analysis of Seven Polyamines in Nephotettix cincticeps by Using Ultra-Performance Liquid Chromatography-Triple Quadrupole Mass Spectrometry - Mingwen Zhang; Yunqiang Zhao; Zongwen Wang; Jintian Cheng (Journal of Analytical Methods in Chemistry)
A fast, simple, and sensitive method for the simultaneous determination of seven polyamines in Nephotettix cincticeps was developed based on ultra-performance liquid chromatography-triple quadrupole mass spectrometry (UPLC-3Q-MS) together with liquid phase extraction. Polyamines in insect samples were extracted with HClO4 solution and then were separated and detected by UPLC-3Q-MS, which was equipped with a hydrophilic interaction liquid chromatography column, within 5 min without any derivatization procedure. The method has been successfully used to detect 7 polyamines in healthy and difluormethylornithine-treated adults of Nephotettix cincticeps with a method limit of detection and the method limit of quantitation of 24–139 pg/mg and 82–464 pg/mg, respectively, an intraday and interday relative standard deviation (RSD, n = 5) of 1.97–6.00% and 2.08–5.92% respectively, and a recovery of 86–115%. The success of this study provided a reliable method for the rapid and high-throughput detection of polyamines in the insect sample.